Design of new acid-activated cell-penetrating peptides for tumor drug delivery - Yao, Jia; Ma, Yinyun; Zhang, Wei; Li, Li; Zhang, Yun; Zhang, Li; Liu, Hui; Ni, Jingman; Wang, Rui (PeerJ, 2017)
TH(AGYLLGHINLHHLAHL(Aib)HHIL-NH2), a histidine-rich, cell-penetrating peptide with acid-activated pH response, designed and synthesized by our group, can effectively target tumor tissues with an acidic extracellular environment. Since the protonating effect of histidine plays a critical role in the acid-activated, cell-penetrating ability of TH, we designed a series of new histidine substituents by introducing electron donating groups (Ethyl, Isopropyl, Butyl) to the C-2 position of histidine. This resulted in an enhanced pH-response and improved the application of TH in tumor-targeted delivery systems. The substituents were further utilized to form the corresponding TH analogs (Ethyl-TH, Isopropyl-TH and Butyl-TH), making them easier to protonate for positive charge in acidic tumor microenvironments. The pH-dependent cellular uptake efficiencies of new TH analogs were further evaluated using flow cytometry and confocal laser scanning microscopy, demonstrating that ethyl-TH and butyl-TH had an optimal pH-response in an acidic environment. Importantly, the new TH analogs exhibited relatively lower toxicity than TH. In addition, these new TH analogs were linked to the antitumor drug camptothecin (CPT), while butyl-TH modified conjugate presented a remarkably stronger pH-dependent cytotoxicity to cancer cells than TH and the other conjugates. In short, our work opens a new avenue for the development of improved acid-activated, cell-penetrating peptides as efficient anticancer drug delivery vectors.
Keywords: Cell-penetrating peptide; PH-sensitivity; TH analogs; Antitumor